Synthesis, Growth and Structural Characterization of Semi Organic Non-Linear Optical Material: L-Arginine Doped Zinc Sulphate Heptahydrate Single Crystal - Krishna Priya, R.; Mary Delphine, S.; Shobana, Sutha (Asian Journal of Chemistry, 2015)
A method of slow evaporation was adopted to grow pure semiorganic non linear L-arginine doped zinc sulphate heptahydrate single crystals. The lattice parameters of the grown crystals were found out using powder XRD pattern. The different functional bond frequencies linked within the crystals were analyzed by FT-IR spectroscopic analysis. The absorption spectrum (UV-visible) between 200-1100 nm illustrates the absorption in this range along with the absence of any combination modes above 270 nm. Further TG/DTA curves ensure the absence of lattice water and thermal stability of the grown crystals. The L-Arginine was added in 0.01, 0.03, 0.05 mole % to zinc sulphate heptahydrate and the compound salts were subjected to Kurtz powder technique technique. It was observed that the second harmonic generation efficiency of 0.03 mole % L-arginine doped zinc sulphate heptahydrate single crystal is very much higher than pure zinc sulphate heptahydrate. The Vickers's micro hardness measurements proved the mechanical stability of the grown crystals.